Vulnerabilidade sócioambiental: mapas afetivos e degradação ambiental no Conjunto Vila Velha, Fortaleza, Ceará - Mesquita, Edson Minarete Pacheco de (2010)
The Vila Velha Housing locates in Fortaleza‟s far west is result of many public politics of housing, by the competition for urban land and environment destruction. To understand how people live in this neighborhood, under which condition they live, the environmental aspects and the neighborhood´s feelings about the place of housing, a research‟s methodology was created in IBGE data analysis grounding about indicator of income, education and housing qualities, at last a social vulnerability rate for Vila Velha Housing was developed. As a result was notice that the majority of population live under high social vulnerability conditions. Through a interactive matrix, the Leopold matrix, the Vila Velha´s environmental aspects was described, the climate, relief, soil, and vegetation was make up showing his environmental vulnerability through his destruction. In parallel approach was used as a analysis tool of affects the affective maps created by BOMFIM (2003), twenty two health agents organized the interviewed group. As a result of the affect‟s research, images of contrast, destruction, pertaining and pleasure arise. The most significant images was contrast and destruction typical traits of negative feelings about Vila Velha Housing, which strengthened our hypothesis that in high socio-environmental places there´s a predominance of negative affects about palces. The Vila Velha Housing locates in Fortaleza‟s far west is result of many public politics of housing, by the competition for urban land and environment destruction. To understand how people live in this neighborhood, under which condition they live, the environmental aspects and the neighborhood´s feelings about the place of housing, a research‟s methodology was created in IBGE data analysis grounding about indicator of income, education and housing qualities, at last a social vulnerability rate for Vila Velha Housing was developed. As a result was notice that the majority of population live under high social vulnerability conditions. Through a interactive matrix, the Leopold matrix, the Vila Velha´s environmental aspects was described, the climate, relief, soil, and vegetation was make up showing his environmental vulnerability through his destruction. In parallel approach was used as a analysis tool of affects the affective maps created by BOMFIM (2003), twenty two health agents organized the interviewed group. As a result of the affect‟s research, images of contrast, destruction, pertaining and pleasure arise. The most significant images was contrast and destruction typical traits of negative feelings about Vila Velha Housing, which strengthened our hypothesis that in high socio-environmental places there´s a predominance of negative affects about palces.